A Study of Undergraduate Students’ Perception about Academic Advising in an Indonesian University - Imelda Junita; Fanny Kristine; Sherlywati Limijaya; Tabita Emmanuella Widodo (Humaniora, 2020)
The aim of the research was to explore undergraduate students’ perceptions about academic advising in an Indonesian university by measuring aspects of academic advising, involving the nature of advising relationship, the frequency of activities occurring during advising sessions, and students’ satisfaction with academic advising. The research applied quantitative research conducted by administering a questionnaire. The sample consisted of 302 undergraduate students who were asked to respond about the type of academic advising they perceived, topics discussed between advisor and student during academic advising sessions, and their satisfaction with academic advising in the university. The results show that the undergraduate students at an Indonesian university perceive their academic advising as ‘developmental advising’ rather than ‘prescriptive advising’. Undergraduate students perceive that the advisors not only focus on academic performance but also students’ holistic development. Most students are satisfied with the academic advising they have experienced. The topics most frequently discussed are related to the registration and course selection, while the topics most rarely discussed are related to institutional policies. In general, 72,85% of students satisfy with the academic advising they have experienced.